2012
DOI: 10.1371/journal.pone.0050211
|View full text |Cite
|
Sign up to set email alerts
|

Disc Volume Reduction with Percutaneous Nucleoplasty in an Animal Model

Abstract: Study DesignWe assessed volume following nucleoplasty disc decompression in lower lumbar spines from cadaveric pigs using 7.1Tesla magnetic resonance imaging (MRI).PurposeTo investigate coblation-induced volume reductions as a possible mechanism underlying nucleoplasty.MethodsWe assessed volume following nucleoplastic disc decompression in pig spines using 7.1-Tesla MRI. Volumetry was performed in lumbar discs of 21 postmortem pigs. A preoperative image data set was obtained, volume was determined, and either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Numerous studies have reported laser ablation with the use of laser as an alternative treatment to spinal surgeries, but the mechanisms of action of laser ablation has not been fully elucidated (2,(8)(9)(10)(11)(12)(13). Studies have shown that the biophysical mechanism of laser involves high-energy ablation which ablates the NP, decreases NP volume, and produces pain relief (7,14,15). A decrease in NP volume may enhance local circulation, whereas an increase in vascular supply stimulates macrophages and migrating macrophages may desiccate the NP.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported laser ablation with the use of laser as an alternative treatment to spinal surgeries, but the mechanisms of action of laser ablation has not been fully elucidated (2,(8)(9)(10)(11)(12)(13). Studies have shown that the biophysical mechanism of laser involves high-energy ablation which ablates the NP, decreases NP volume, and produces pain relief (7,14,15). A decrease in NP volume may enhance local circulation, whereas an increase in vascular supply stimulates macrophages and migrating macrophages may desiccate the NP.…”
Section: Discussionmentioning
confidence: 99%
“…However, more proponents and clinical evidence supported nucleoplasty for individual with lumbar radicular pain, 26 , 27 because of decompression of nerve root through removing nucleus material, decreasing nucleus volume and lowering intradiscal pressure. 28 , 29 In contrast, the benefit of coblation nucleoplasty in treating discogenic low back pain is uncertain, because the scope of interruption of nerves hardly reached to the outer annulus, which was considered as the major origin of discogenic pain. 8 …”
Section: Discussionmentioning
confidence: 99%
“…The possible explanation is that lowering the tension in the outer annulus is benefit for decompression of nerves innervated the outer annulus. 28 , 29 Additionally, the modification of biochemical state to inhibit inflammatory stimulation to nerves innervated the outer annulus maybe play one therapeutic role in treating discogenic pain. 30 …”
Section: Discussionmentioning
confidence: 99%
“…The usual general contraindications are the same as for any surgical procedure and include fever, infection, bleeding diathesis, and anticoagulant therapy. Vaporization of nuclear material by creating multiple intradiscal channels during coblation with the device wand should result in reduction of nuclear tissue volume and lead to a decrease in intradiscal pressure that can result in pain reduction. The patient usually does not feel discomfort during the procedure, because the coblation and coagulation take place within the nucleus pulposus, which contains little sensory innervation.…”
Section: Interventional Options For Diagnosis and Treatment Of Low Bamentioning
confidence: 99%